Is action understanding an automatic process? Both cognitive and perceptual processing are required for the identification of actions and intentions - Thompson, E; Long, E; Bird, GP; Catmur, C (SAGE Publications, 2022)
The ability to identify others’ actions and intentions, “action understanding,” is crucial for successful social interaction. Under direct accounts, action understanding takes place without the involvement of inferential processes, a claim that has yet to be tested using behavioural measures. Using a dual-task paradigm, the present study aimed to establish whether the identification of others’ actions and intentions depends on automatic or inferential processing, by manipulating working memory load during performance of a task designed to target the identification of actions and intentions. Experiment 1 tested a novel action understanding task targeting action identification and intention identification. This task was then combined with two working memory manipulations (cognitive: Experiment 2; perceptual: Experiment 3) to determine whether action identification and intention identification are disrupted by concurrent cognitive or perceptual load. Both action identification and intention identification were impaired by concurrent cognitive and perceptual processing, indicating that action understanding requires additional perceptual and cognitive resources. These findings contradict a direct account of action understanding.